PENGARUH POLA ASUH ORANG TUA DAN LINGKUNGAN PENDIDIKAN TERHADAP MOTIVASI BELAJAR SISWA SMP DI KECAMATAN SAHU, KABUPATEN HALMAHERA BARAT - DEO, ANDRI; KEMPA, RUDOLF; SAHALESSY, ARNOLD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Parenting Patterns and the Educational Environment are factors to be considered in order to increase students' learning motivation. This research was conducted with the aim of seeing the extent of the influence of parental parenting and the educational environment on students' learning motivation. The type of research carried out in this research is quantitative research with the number of samples selected using the saturated sampling technique being 93 people. The technique used to obtain data is through a closed questionnaire.Descriptive statistics show that (1) Parenting Patterns in Middle Schools in Sahu District, are in the high category at 100%; (2) The educational environment in junior high schools in Sahu District, is in the very high category at 79.22%, in the high category at 20.78%; (3) Students' learning motivation in junior high schools in Sahu District, Province is in the very high category at 70.13%, in the high category at 29.87%.Regression test statistics show that (1) There is an influence of parenting patterns on junior high school students' learning motivation in Sahu District. This influence can be explained through the regression model formed, namely ý = 93.718 + 0.158x1. The magnitude of the influence of parenting style on student learning motivation, namely 11% and 89%, is another factor outside this regression model; (2) There is an influence of the educational environment on the learning motivation of junior high school students in Sahu District. This influence can be explained through the regression model formed, namely ý=121.567 + (-0.114x2). The magnitude of the influence of the educational environment on student learning motivation is 0.071 or 7.1% and the remaining 92.9% is other factors outside this regression model; and (3) there is a positive and significant influence of parenting styles and the educational environment on junior high school students' learning motivation in Sahu District. This influence can be explained through the regression model formed, namely ý=106.676 + 0.215x1 + 0.171x2. The influence of parenting patterns and the educational environment on student learning motivation is 25.70% and the remaining 74.30% is other factors outside this regression model. ABSTRAKPola Asuh Orang Tua dan Lingkungan Pendidikan menjadi faktor yang hendak diperhatikan dalam rangka peningkatan motivasi belajar pada siswa. Penelitian ini dilakukan bertujuan untuk melihat sejauh mana pengaruh pola asuh orang tua dan lingkungan pendidikan terhadap motivasi belajar siswa. Jenis penelitian yang dilakukan dalam penelitian ini adalah penelitian kuantitatif dengan jumlah sampel yang terpilih dengan teknik sampel penuh adalah 93 orang. Teknik yang digunakan untuk memperoleh data melalui angket yang bersifat tertutup. Statistik deskriptif menunjukan bahwa (1) Pola Asuh Orang Tua pada SMP di Kecamatan Sahu pada kategori tinggi sebesar 100%; (2) Lingkungan Pendidikan pada SMP di Kecamatan Sahu pada kategori sangat tinggi sebesar 79,22%, kategori tinggi sebesar 20,78%; (3) Motivasi Belajar Siswa pada SMP di Kecamatan Sahu, pada kategori sangat tinggi sebesar 70,13%, kategori tinggi sebesar 29,87%.Statistik uji regresi menunjukan bahwa (1) Terdapat pengaruh dari Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa SMP di Kecamatan Sahu. Pengaruh ini dapat dijelaskan melalui Model regresi yang terbentuk yaitu ý = 93,718 + 0,158x1. Besar pengaruh pola asuh orang tua terhadap motivasi belajar siswa yaitu 11% dan 89% adalah faktor lain diluar model regresi ini; (2) Terdapat pengaruh dari Lingkungan Pendidikan terhadap Motivasi Belajar Siswa SMP di Kecamatan Sahu. Pengaruh ini dapat dijelaskan melalui Model regresi yang terbentuk yaitu ý=121,567 + (-0,114x2). Besar pengaruh Lingkungan Pendidikan terhadap Motivasi Belajar Siswa yaitu sebesar 0,071 atau 7.1 % dan sisanya 92,9 % adalah factor lain-lain diluar model regresi ini; dan (3) terdapat pengaruh positif dan signifikan dari Pola Asuh Orang Tua dan Lingkungan Pendidikan terhadap Motivasi Belajar Siswa SMP di Kecamatan Sahu. Pengaruh ini dapat dijelaskan melalui Model regresi yang terbentuk yaitu ý=106,676 + 0,215x1 + 0,171x2. Besar pengaruh Pola Asuh Orang Tua dan Lingkungan Pendidikan terhadap Motivasi Belajar Siswa yaitu sebesar 25,70% dan sisanya 74,30% adalah faktor lain-lain di luar model regresi ini.